Computer aided math learning as a tool to assess and increase motivation in learning math by visually impaired students. (4th July 2022) - Maćkowski, Michał; Żabka, Marek; Kempa, Wojciech; Rojewska, Katarzyna; Spinczyk, Dominik
Abstract: Purpose: Effective teaching and learning mathematics is important to achieve good results during an academic and professional career. This is especially difficult for visually impaired students because of difficulties in managing structural information included in maths formulae. Methods: The extended multimedia alternative method, including the problem of decomposition and knowledge vector, were presented and compared to the classical teaching method. A qualitative method to evaluate motivation during the process of teaching and learning maths for impaired students, which includes eleven detailed motivators, has been developed. Results: The alternative teaching method offers statistically significant improvements in four of the eleven proposed assessment categories: success in progress – adjusting the difficulties of learning, presentation of the material, approval: group/individual and alternative presentation of mathematic materials. The experiments carried out allowed the authors to increase the knowledge about the limitations and challenges occurring in the process of maths education among visually impaired students and their motivation. Conclusions: Based on the experiments and research results, it can be concluded that applying the proposed method of decomposition together with evaluation procedure based on the vector of knowledge in the process of teaching and learning of mathematics by visually impaired may increase their motivation positively. Implications for Rehabilitation: The key aspects of the alternative method of presenting math formulae are included in the bellow points:  It increases the availability of materials containing structured information (mathematical formulae) for the blind.  It limits the importance of communication barriers in math education: the possibility of self-study, reducing costs – by reducing the number of individual tutorials.  It contributes to the development of universal rules for the structural presentation of information  It increases the independence of the student from the teacher.